Materiały do ustalenia wschodniej granicy zasięgu kwaśnej dąbrowy trzcinnikowej Calamagrostio arundinaceae-Quercetum petraeae (Hartm. 1934) Scam. et Pass. 1959 w Polsce – dwa nowe stanowiska zespołu na południu województwa mazowieckiego - Zaniewski, Piotr; Ciurzycki, Wojciech; Marciszewska, Katarzyna (Leśne Prace Badawcze, 2020)
Acidophilous oak forests Calamagrostio arundinaceae-Quercetum petraeae (Hartm. 1934 Scam. et Pass. 1959) are mostly known from the western part of Poland, while its eastern border has not been determined accurately. In order to address this issue, we performed a phytosociological analysis of two newly identified stands of acidophilous oak forest located in the southern part of the Mazovian Voivodeship near Kiedrzyn (vicinity of Nowe Miasto nad Pilicą) and Mikówka (vicinity of Białobrzegi). For comparison, we also examined the distribution of known patches in the region (Łódź and Mazovian Voivodeships) against this association’s background of the eastern range border. Within the identified sites, a total of 10 phytosociological relevés were taken and soil samples were collected from a depth of 10 cm. The content of organic matter, soil pH and sieving analysis were performed in the laboratory. The phytosociological material was ordered and numerically classified to obtain a division into two groups of relevés: typical for this association (seven relevés) and a degenerated form (three relevés), which has an increased share of pine in the stand. All our relevés were similar to acidophilous oak forests from the Wielkopolska region and thus different from oak-pine forests of eastern Poland. Habitat conditions of the patches and the bonitation of oak were analogous to patches of this association from other parts of Poland. Furthermore, the sites we studied are located between known locations from the Bolimowska and Kozienicka Forests and are therefore connecting these two previously known areas of occurrence. This indicates that the range of the Calamagrostio-Quercetum association is at least a few dozen kilometers wider in this part of the country than the assumed range.